2018
DOI: 10.3389/fbioe.2018.00103
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cells From the Apical Papilla (SCAP) as a Tool for Endogenous Tissue Regeneration

Abstract: Stem cells extracted from developing tissues possibly exhibit not only unique but also superior traits against their developed counterparts. Indeed, stem cells from the apical papilla (SCAP); a unique group of dental stem cells related to developing roots have been shown to be a promising tool for regenerative endodontic procedures and regeneration in general. Studies have characterized the phenotypic traits as well as other regenerative potentials of these cells. Specific sub-populations have been highlighted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
83
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(86 citation statements)
references
References 55 publications
(196 reference statements)
2
83
0
1
Order By: Relevance
“…[4][5][6]. It has been suggested that MSCs may be present virtually in any vascularized tissue [7], so the expression of the aforementioned markers, indicative of MSC nature, reflect the perivascular location and multilineage differentiation potential of SCAPs [8]. In addition, it has been described that SCAPs are capable of exhibiting a variety of osteo/dentinogenic markers (BSP, DSPP, ALP, Runx2, MEPE) [9][10][11], and reports have shown different degrees of root maturation after disinfection in cases with severely infected pulps in immature teeth [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6]. It has been suggested that MSCs may be present virtually in any vascularized tissue [7], so the expression of the aforementioned markers, indicative of MSC nature, reflect the perivascular location and multilineage differentiation potential of SCAPs [8]. In addition, it has been described that SCAPs are capable of exhibiting a variety of osteo/dentinogenic markers (BSP, DSPP, ALP, Runx2, MEPE) [9][10][11], and reports have shown different degrees of root maturation after disinfection in cases with severely infected pulps in immature teeth [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with dental pulp stem cells (DPSCs), they have a higher expression of telomerase, a superior proliferation rate and dental tissue regeneration capacity [6][7][8]. They express surface markers common to other dental stem cells, like STRO-1, but also a distinctive marker, CD24 [9]. SCAPs also express Survivin, a protein which plays a significant role in cell proliferation [7,10].…”
Section: Introductionmentioning
confidence: 99%
“…Since SCAPs are derived from the immature structure, they express primitive embryonic markers such as Sox2, Oct3/4 and Nanog accompanied with typical MSC markers [81,87]. Among those markers, co-expression of CD146 and STRO-1 is found to be related to early MSCs; indeed, CD146+/STRO-1 + SCAPs exhibit superior colony-forming efficiency with increased cumulative doubling than counterpart [88]. CD24, another marker for the pluripotent population, is regarded as a representative surface marker for SCAPs because of its absence in other dental MSCs [89].…”
Section: Apical Papilla Stem Cells (Apscs)mentioning
confidence: 99%